Microstructural investigation of thermo-mechanically processed lithium slag for geopolymer precursor using various characterization techniques - Javed, Usman; Shaikh, Faiz; Sarker, Prabir Kumar (ELSEVIER SCI LTD, 2022)
Lithium slag is an emerging industrial waste due to the increasing demand for lithium rechargeable batteries attributed to the recent boom in the automobile industry and space exploration. It is extracted as a powder residue in sedimentary tanks after the refining process of lithium extraction. In this study, the effect of thermo-mechanical processing on the chemical reactivity of lithium slag is assessed by TESCAN Integrated Mineral Analyzer (TIMA), X-ray Fluorescence (XRF), Rietveld quantitative refinement techniques. The chemical, mineral, and crystallographic phase composition of processed lithium slag specimens were assessed and compared by XRF, TIMA, and Rietveld quantitative refinement techniques, respectively. The results of thermo-mechanical processing indicated that the mineral and crystallographic transformation of Spodumene to feldspars (Anorthite, Muscovite, Albite) occurred by crystallite agglomeration. The chemical reactivity of lithium slag is gauged in terms of amorphous alumino-silicates present in feldspars and unidentified phases. Characterization of unidentified phase is evident that it majorly contains micro-nano sized alumino-silicate rich particles with similar spectral signatures to that of feldspar, some fraction of it is aggregated into other phases due to its reactivity. The concentration of the amorphous phase is proportionate with the thermo-mechanical processing energy. However, the thermo-mechanical processing energy is also optimized based on the generation of amorphous phase and reduction in particle size. Therefore, the G1C700 processed regime resulted in one of the maximum amounts of amorphous phase (52.60%). The mineral phase transformation of Spodumene to Anorthite (+10.46%) and unidentified phase (+8.24%) along with D50 value of 13.26 µm, consequently releasing 0.45 kg of carbon emissions upon thermo-mechanical processing. Hence, G1C700 lithium slag is recommended for its use as a geopolymer precursor.